Performance of Periwinkle Shell Ash Blended Cement Concrete Exposed to Magnesium Sulphate - Umoh, A.A.; Olusola, K.O. (Institute of Research and Community Outreach - Petra Christian University, 2013)
The study examined the compressive strength of periwinkle shell ash (PSA) blended cement concrete in magnesium sulphate medium. Specimens were prepared from designed characteristics strength of 25 MPa. The cement replacement with PSA ranged between 0 and 40% by volume. A total of 180 cube specimens were cast and cured in water. At 28 days curing, 45 specimens each were transferred into magnesium sulphate of 1%, 3%, and 5% solution, while others were continuously cured in water and tested at 62, 92, and 152 days. The results revealed a higher loss in compressive strength with the control mix, and that it increases with increased in MgSO4 concentration and exposure period, whereas, the attack on the PSA blended cement concrete was less and the least value recorded by 10% PSA content. Therefore, the study concluded that the optimum percentage replacement of cement with 10% PSA could mitigate magnesium sulphate attack.